Structure and floristic composition of one of the last forest fragments containing the critically endangered Northern Muriqui (Brachyteles Hypoxanthus, Primates) - Boubli, Jean Philippe; Couto, Fabiana; Strier, Karen B. (Ecotropica, 2011)
This study presents results from the first systematic botanical investigation of the RPPN Feliciano Miguel Abdala (RPPN-FMA, formerly Caratinga Biological Station), a semi-deciduous forest fragment in southeastern Brazil that supports nearly a third of the remaining population of the critically endangered northern muriqui (BrachyteUs hypoxanthus). Here we describe the structure, diversity, and floristic composition of this forest. Our goal was to provide the scientific basis for a management plan that will take into consideration the factors involved in the unusually high muriqui carrying capacity in this fragment. Our sample comes from six 500 × 10 -m plots, totaling 3 ha. We marked and identified all trees with DBH ≥ 10 cm in all of the plots, and all trees of 5 ≤ DBH < 10 cm in half of the plots (1.5 ha). Forest structure was consistent with secondary forest characteristics, inasmuch as large trees were rare, total basal area was small, canopy was discontinuous, average tree height was low, and liana load was heavy. Top-ranking families, based on Importance Value, were Fabaceae, Euphorbiaceae, Annonaceae, Rubiaceae, and Moraceae. Compared with other forests where northern muriquis occur, the RPPN-FMA forest was more floristically diverse (H' = 4.6) and even (J = 0.85). In addition, top- ranking species were known muriqui foods. These factors might contribute to the unusually high density of the primate found at this site. © Society for Tropical Ecology.